2020
DOI: 10.22541/au.158981496.67744667
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Co-Infection of Mycoplasma hyopneumoniae and other swine pathogens

Abstract: Mycoplasma hyopneumoniae (M. hyopneumoniae, Mhp) is an etiological agent that causes mycoplasma pneumonia of swine (MPS), this is a chronic respiratory disease present in every major swine-producing country worldwide. It is well elucidated, Mhp infections may downregulate the host immune system and enhance the infection and replication of other pathogens. However, the mechanisms of interaction between Mhp and other pathogens is still missing. Though, additional studies have reported that several cofactors such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 101 publications
(120 reference statements)
1
4
0
Order By: Relevance
“…In accordance with our results, investigations of lungs from slaughtered pigs in France also reported that P. multocida was more likely to be detected in M. hyopneumoniae-positive lungs [63]. Especially, M. hyopneumoniae and P. multocida coinfections are frequently described in pigs with respiratory disease [34,37,63]. In contrast to our findings, investigations of lungs from slaughter pigs revealed no correlation between detection of M. hyopneumoniae and M. hyorhinis, while another study examining BALF samples from pigs with respira-tory problems reported a positive association [34,70].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In accordance with our results, investigations of lungs from slaughtered pigs in France also reported that P. multocida was more likely to be detected in M. hyopneumoniae-positive lungs [63]. Especially, M. hyopneumoniae and P. multocida coinfections are frequently described in pigs with respiratory disease [34,37,63]. In contrast to our findings, investigations of lungs from slaughter pigs revealed no correlation between detection of M. hyopneumoniae and M. hyorhinis, while another study examining BALF samples from pigs with respira-tory problems reported a positive association [34,70].…”
Section: Discussionsupporting
confidence: 91%
“…Thus, the isolation of either pathogen remains difficult to interpret. However, there is evidence that in case of concurrent infections, symptoms and lung lesions are more severe compared to monoinfections [6,34,37,38]. While P. multocida and S. suis grow easily on sheep-blood agar plates, B. bronchiseptica often gets overgrown by other bacteria, emphasizing the need for selective media for proper isolation [36].…”
Section: Introductionmentioning
confidence: 99%
“…Disease may be caused by a single organism, but co-infections can also occur with two bacteria or a bacterium and a virus [35,36]. Within the context of animal production, these co-infections make it difficult to identify the culprit.…”
Section: Microorganisms To Control In Pigsmentioning
confidence: 99%
“…Within the context of animal production, these co-infections make it difficult to identify the culprit. Indeed, biological interactions between microorganisms are likely to influence both the clinical symptoms observed by the producers and the severity of the infection [36]. When an infection occurs, the pathogen is qualified as a primary etiologic agent when it causes the disease.…”
Section: Microorganisms To Control In Pigsmentioning
confidence: 99%
See 1 more Smart Citation